Transient Liquid Phase Bonding of AlN to AlSiC for Durable Power Electronic Packages. Issue 10 (12th June 2018) - Pahinkar, Darshan G.; Puckett, Waylon; Graham, Samuel; Boteler, Lauren; Ibitayo, Dimeji; Narumanchi, Sreekant; Paret, Paul; DeVoto, Douglas; Major, Joshua
Abstract : Conventional power electronic modules employ a direct bonded copper (DBC) substrate and multiple interface layers to dissipate heat. However, reliability issues arise due to the coefficient of thermal expansion (CTE) mismatch that exists between the metal, ceramic, and semiconductor materials in the conventional module. Significant performance enhancement can be achieved by eliminating the DBC and developing an integrated substrate/cold plate with a low CTE mismatch throughout the package. To address this need, we have demonstrated the ability to directly bond the aluminum nitride (AlN) substrate to an AlSiC heat sink through transient liquid phase bonding using a Cu–Al binary system. Fabricated samples are found to have good interfacial adhesion. The novel bond material exhibits properties analogous to AlSiC and is analyzed for thermal, mechanical, and metallographic properties. The novel structure demonstrated in this work will enable smaller, lighter, and more reliable power modules, when compared to traditional configurations. Abstract : We have demonstrated the ability to directly bond the aluminum nitride (AlN) substrate to an AlSiC heat sink through transient liquid phase bonding using a Cu–Al binary system at 565 °C without any gaseous environment. Fabricated samples are found to have good interfacial adhesion. The novel structure in this work will enable smaller, lighter, and more reliable power modules.